Women's acute anxiety variations before and after epidural anesthesia for childbirth - Francisco J. Fernández-Campos; Dolores Escrivá; José M. Palanca; Francisca Ridocci; Carlos Barrios; Juan Gallego (Taylor & Francis Group, 2017)
Objective: This study assessed changes in anxiety during different phases of childbirth in a sample of women demanding epidural anesthesia. Design: Prospective, longitudinal case series. Sample: A total of 133 women who demanded epidural anesthesia for childbirth answered the questionnaires. Methods: Anxiety state was measured using the State Trait Anxiety Inventory (STAI) questionnaire. The STAI-S (anxiety state) was administered in three phases during childbirth: Phase 1 was before applying epidural anesthesia, Phase 2 was 45 min after the application of epidural anesthesia and Phase 3 was at less than 24 h after delivery. Data were collected in two general hospitals: a third-level public hospital and a well-recognized private hospital. Main outcome measures: STAI scores. Results: Anxiety state decreases significantly after applying the epidural anesthesia (Phase 2) compared to before anesthesia (Phase 1), and it remains low levels 24 h after childbirth (Phase 3). There were statistically significant differences in STAI scores between the different phases administrated (Phases 1 and 2: p < 0.001; effect size, d = 1.40; Phases 1 and 3: p < 0.001; effect size, d = 1.39). In Phase 3, women with cesarean section birth had significant differences in STAI scores relative to those with spontaneous birth (p = 0.037; d = 0.44). The type of health-care setting (public or private), the educational level and the numbers of previous births does not affect the level of anxiety state in women in any of the three phases. Conclusions: Women's anxiety decreases significantly after applying epidural anesthesia, and it remains low 24 h after delivery. Anxiety against childbirth was not influenced by the health system used by women, by the condition of primiparous or multiparous, or by the educational level. Women who received an epidural anesthesia with a cesarean section reported higher rates of anxiety state after birth.